2018
DOI: 10.1521/jscp.2018.37.6.431
|View full text |Cite
|
Sign up to set email alerts
|

Attributions for Rejection and Acceptance in Young Adults With Borderline and Avoidant Personality Features

Abstract: Individuals with borderline and avoidant personality disorders show interpersonal dysfunction that includes maladaptive responses to rejection and reduced emotional benefits from acceptance. To identify the attributional styles that may underlie these difficulties, we examined causal attributions for rejection and acceptance among undergraduates high in features of each disorder and a healthy comparison group. In Study 1, participants rated how likely they were to attribute hypothetical rejection and acceptanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Two studies did not report recruitment methods. Of note, one study recruited a community sample with high levels of self‐reported BPD features (Berenson, Nynaes, Wakschal, Kapner, & Sweeney, ). Studies differed in the inclusion of individuals undergoing BPD treatment.…”
Section: Resultsmentioning
confidence: 97%
“…Two studies did not report recruitment methods. Of note, one study recruited a community sample with high levels of self‐reported BPD features (Berenson, Nynaes, Wakschal, Kapner, & Sweeney, ). Studies differed in the inclusion of individuals undergoing BPD treatment.…”
Section: Resultsmentioning
confidence: 97%
“…These negative cognitions seem to deteriorate agency and foster underachievement ( Coon, 1994 ); “I will not be able to do things my way, and I will fail, why bother trying” ( Videler et al, 2017 ). They hold back in fear of others’ critique ( Nordahl and Stiles, 2000 ; Arntz et al, 2011 ; Bowles et al, 2013 ; Eikenæs et al, 2013 ; Rees and Pritchard, 2015 ; Berenson et al, 2018 ; Flink et al, 2019 ). Self-critique rapidly follows attempts to articulate needs, keeping agency low ( Inchausti et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, many patients with severe PDs suffered from severe relational stress traumas during critical developmental periods, stress traumas which were often also associated with focal traumas such as sexual and physical abuse, and emotional abuse and neglect (Howell & Blizard, 2009; Mosquera & Steele, 2017). These traumas are seen as having caused a severe impairment in the sense of interpersonal safety, contributing to frequent states of hypervigilance associated with a difficulty in downregulating emotions (Berenson, Nynaes, Wakschal, Kapner, & Sweeney, 2018; Bertsch et al, 2017; Fertuck, Fischer, & Beeney, 2018; Masland & Hooley, 2019; Schilling, Moritz, Schneider, Bierbrodt, & Nagel, 2015). Moreover, such traumas engender pathogenic beliefs that support a strong self-hate (Faccini & Gazzillo, in press).…”
Section: Understanding Severe Personality Pathology Through the Lens ...mentioning
confidence: 99%